Entrance Examination for Master of Music Program in China - Guolin , Tu; Sukhumvat, Songphon (Journal of Roi Kaensarn Academi, 2024)
Music major is one of the important art subjects in colleges and universities. There are currently 138 colleges and universities in the country recruiting master's degree students in music major. With the increase in the number of colleges and universities enrolling students for music master's degree in my country, in order to improve their learning efficiency, professional skills and examination success rate, more and more candidates will enter music postgraduate entrance training institutions or specifically ask relevant professional teachers for tutoring and study, and strengthen their theoretical knowledge and professional skill. However, most candidates will choose a music postgraduate entrance examination training institution that suits them, and systematically receive professional theoretical learning and professional skills training from the training institution. This article presented the Entrance Examination for Master of Music Program in China.